Nutritional profile optimisation of carbon dioxide fixing bacteria by molecular engineering - Mortimer, Zahara (2024)
A global dilemma has evolved concerning the sustainability of supplying global energy demand and feeding a growing global population, predicted to increase by 2 billion towards 2050. The production of greenhouse gases (GHG) driven by anthropogenic activity is the dominant contributor to the global climate change effect observed, with energy related carbon dioxide (CO2) emissions remaining at their highest in 2022 since before 1990. Simultaneously, approximately 10 % of the current global population suffer from hunger, despite one third of food resources being wasted annually. The capacity of bacteria to biologically sequester CO2 whilst generating a protein source offers a potential strategy to alleviate the energy and food insecurity dilemma described. Cupriavidus necator H16 is a model bacteria capable of fixing CO2 using hydrogen (H2) as an energy source, hence is referred to as a hydrogen oxidising bacteria (HOB). Further, C. necator H16 is amenable to genetic modification with various molecular tools available to optimise the strain, conferring the strain’s potential as a CO2 utilising production chassis. Alternative protein sources derived from bacteria, denoted single cell protein (SCP), are attractive due to their ability to utilise waste as feedstocks, minimal arable land requirement and potential to achieve high protein yields. Notably, this research project was conducted in collaboration with the carbon recycling biotechnology company, Deep Branch®, whose platform is centralised around harnessing CO2 fixing bacteria to generate an optimised protein product, Proton™, for animal feed.